Pengaruh Manajemen Kepala Madrasah Dalam Meningkatkan Mutu Pembelajaran Di MTsN 13 Jombang Tahun 2020 - Ahmad Fawaid Musthofal Arif; Fatkhulloh Abdul Malik; Muhamad Khoirur Roziqin (JoEMS (Journal of Education and Management Studies), 2022)
The purpose of this study was to determine the form of the madrasa principal's strategy in improving the quality of learning at MTsN 13 Jombang. This type of research is a field research with a qualitative approach. The method used is participatory observation. Data collection is done through observation, interviews, documentation. The technical analysis of data with data collection, data reduction, data presentation, verification and drawing conclusions. The results of this study indicate that the principal of the madrasa is right to use a strategy that has been planned in advance to improve the quality of learning at MTsN 13 Jombang. However, there are still less infrastructure facilities such as classes. The principal's efforts continue to provide space for the implementation of learning to remain effective even though learning is carried out in the prayer room. In addition, the obstacle that occurs in improving the quality of learning is the lack of subject teacher resources. The results obtained from the strategy designed by the principal were able to make students more active in class during the learning process as evidenced by the student's score being able to achieve the KKM score. Not only that, a positive response from the community towards Mts Negeri 13 Jombang was also obtained and became the motivation to further improve the quality of education in the madrasa. This is shown from the results of interviews and observations with the principal and staff of MtsN 13 Jombang.